2020
DOI: 10.1192/bjo.2019.97
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk model to predict 28-day unplanned readmission via the accident and emergency department after discharge from acute psychiatric units for patients with psychotic spectrum disorders

Abstract: Background Unplanned readmissions rates are an important indicator of the quality of care provided in a psychiatric unit. However, there is no validated risk model to predict this outcome in patients with psychotic spectrum disorders. Aims This paper aims to establish a clinical risk prediction model to predict 28-day unplanned readmission via the accident and emergency department after discharge from acute psychiatric units for patients with psychotic spectrum disorders. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Although previous evidence reached consensus that older adults encountered more ED returns when compared with younger adults, the increasing age, within the spectrum of the older population, has yet demonstrated contradictory results. Some studies coincided with our finding that the oldest old were less prone to re-visit, [33][34][35] whereas others concluded that the likelihood of returning to EDs increased concurrently with advancing age. 5,11,13,28 Such inconsistencies in the age effect highlight the importance of considering factors that can more accurately reflect biological or functional age (eg, frailty) rather than simply chronological age in the geriatric population evaluation.…”
Section: Discussionsupporting
confidence: 85%
“…Although previous evidence reached consensus that older adults encountered more ED returns when compared with younger adults, the increasing age, within the spectrum of the older population, has yet demonstrated contradictory results. Some studies coincided with our finding that the oldest old were less prone to re-visit, [33][34][35] whereas others concluded that the likelihood of returning to EDs increased concurrently with advancing age. 5,11,13,28 Such inconsistencies in the age effect highlight the importance of considering factors that can more accurately reflect biological or functional age (eg, frailty) rather than simply chronological age in the geriatric population evaluation.…”
Section: Discussionsupporting
confidence: 85%
“…Patients with a history of violence were also significantly associated with UHRs (OR = 1.30; 95% CI 1.09–1.55) (Hariman et al . 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The items are ‘Overactive, aggressive, disruptive or agitated’ (Hariman et al . 2020), ‘Grandiosity’ and ‘Suspiciousness’ (Hamilton et al . 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the emergence of the ML algorithm, 29 out of 36 articles adopted traditional statistical methods. Among these studies, ~ 90% used LR either as a baseline [ 56 , 58 , 60 , 62 64 , 68 , 73 , 74 , 76 78 , 83 , 85 87 ] or the main model in prediction [ 60 , 69 , 71 , 82 , 88 90 ], and 3 studies derived their own risk scores on the basis of LR variable coefficients [ 61 , 66 , 84 ]. In the remaining 3 papers, the prognosis of readmission was carried out with Cox regression survival analysis.…”
Section: Application To Readmissionmentioning
confidence: 99%